Fairy Tail. 39 - Mashima, Hiro, 1977- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2014)
A lunar eclipse presages an invasion by 10,000 dragons, while humanity finds its only hope the Eclipse Cannon.